The Yiddish historians and the struggle for a Jewish history of the Holocaust - Smith, Mark Lee, 1957- (Detroit, Michigan : Wayne State University Press, 2019)
"The Yiddish Historians and the Struggle for a Jewish History of the Holocaust identifies the Yiddish historians who created a distinctively Jewish approach to writing Holocaust history in the early years following World War II. Author Mark L. Smith explains that these scholars survived the Nazi invasion of Eastern Europe, yet they have not previously been recognized as a specific group who were united by a common research agenda and a commitment to sharing their work with the worldwide community of Yiddish-speaking survivors".
Preface -- Introduction: Writing Jewish history in Yiddish -- The Yiddish historians of the Holocaust -- Becoming Yiddish historians of the Holocaust -- No silence in Yiddish -- Holocaust history as Jewish history -- The search for answers -- The transmission of a culture -- Concluding thoughts.
Includes bibliographical references (p. 319-440) and index.
Keywords: Holocaust, Jewish (1939-1945) -- Historiography; Jewish historians; Yiddish language